2010
DOI: 10.1177/1367493509347058
|View full text |Cite
|
Sign up to set email alerts
|

Marking the 50th anniversary of the Platt Report: from exclusion, to toleration and parental participation in the care of the hospitalized child

Abstract: This paper commemorates the 50th anniversary of the Platt Report in the United Kingdom and traces the history of parental hospital visiting in relation to its recommendation that, 'Parents should be allowed to visit whenever they can, and to help as much as possible with the care of the child' (Ministry of Health, 1959: 38). It tracks how this goal was achieved and identifies how parents moved from being excluded towards being tolerated and finally accepted as participants in their child's care. This is set ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 30 publications
0
29
1
3
Order By: Relevance
“…In the Nordic countries, children have the right to have at least one of their parents with them during a hospital stay (Davies, 2010). Taking the parents into the hospitals during the child's admission has been encouraged both by family interest groups and by professionals over the last decades (Stremler, Wong, & Parshuram, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the Nordic countries, children have the right to have at least one of their parents with them during a hospital stay (Davies, 2010). Taking the parents into the hospitals during the child's admission has been encouraged both by family interest groups and by professionals over the last decades (Stremler, Wong, & Parshuram, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The literature clearly supports the fact that involving patients and/or families in care improves patient outcomes, particularly patient satisfaction. [33][34][35][36] Small Cycles of Change Goal Sheets Daily patient goal sheets were used on the unit before initiation of the IHI project; however, the use was sporadic and lacked standardization of content as well as patient/parent involvement. Up to that time, daily goals were written on letter-sized paper that was posted on a bedside bulletin board.…”
Section: Phasementioning
confidence: 99%
“…Those studies also showed that hospitalized infants were typically separated from their families; remained bedridden and inactive; rarely received analgesia or anaesthesia; and had prolonged hospital stays. Such studies prompted changes in the practices related to the hospitalization of infants, the most important change being that mothers are now allowed to keep their babies with them day and night (a practice known as "rooming-in") during the immediate post-partum period, as well as being allowed to be present throughout the hospitalization of the infant 27 .…”
Section: Introductionmentioning
confidence: 99%